2018
DOI: 10.1111/avj.12660
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and toxin gene distribution among serovars of Actinobacillus pleuropneumoniae from Australian pigs

Abstract: Objective To explore the diversity among isolates of the Actinobacillus pleuropneumoniae serovars most common in Australia (serovars 1, 5, 7 and 15) and to examine the Apx toxin profiles in selected representative isolates.Design A total of 250 isolates selected from different farms were examined for their genotypic profiles and a subset of 122 isolates for their toxin profiles.Methods The isolates of serovars 1, 5, 7 and 15 selected for this study came from different farms and different Australian states and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…In the current study, we used ERIC PCR, which has been used for studies of the diversity of other members of the family Pasteurellaceae, including Haemophilus parasuis and A. pleuropneumoniae. 13,18 Four different patterns were distinguishable among the nine isolates we examined. As these nine isolates came from a single host species and only two farms, a greater diversity might be expected if more cattle from more farms were examined.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the current study, we used ERIC PCR, which has been used for studies of the diversity of other members of the family Pasteurellaceae, including Haemophilus parasuis and A. pleuropneumoniae. 13,18 Four different patterns were distinguishable among the nine isolates we examined. As these nine isolates came from a single host species and only two farms, a greater diversity might be expected if more cattle from more farms were examined.…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, we used ERIC PCR, which has been used for studies of the diversity of other members of the family Pasteurellaceae , including Haemophilus parasuis and A. pleuropneumoniae . Four different patterns were distinguishable among the nine isolates we examined.…”
Section: Discussionmentioning
confidence: 99%
“…I also need to make an apology to our pig veterinarians, if I inadvertently caused you some unintended worry in our January/February issue this year. We published a paper on Actinobacillus pleuropneumoniae in Australia pigs . Unfortunately, due to an editorial mishap, the pointer on the front cover said “Genetic diversity in porcine virus”.…”
Section: Erratum – or Is It A Corrigendum?mentioning
confidence: 99%
“…We published a paper on Actinobacillus pleuropneumoniae in Australia pigs. 10 Unfortunately, due to an editorial mishap, the pointer on the front cover said "Genetic diversity in porcine virus". Many thanks to eagle-eyed readers who pointed out that we were not reporting on a newly discovered virus disease.…”
Section: Production Animalsmentioning
confidence: 99%
“…A genetic study in Australian pigs highlights the need for more research into the variability in virulence of serovars of Actinobacillus pleuropneumoniae. 3 This organism is responsible for porcine pleuropneumonia, and the virulence of each serovar is related to the combination of the haemolytic and cytotoxic exotoxins that they produce. Using ERIC-PCR, this genetic study found wide variation in the toxin patterns in Australian serovars.…”
Section: Production Animalsmentioning
confidence: 99%